Zina, Transnational Feminism, and the Moral Regulation of Pakistani Women: By Shahnaz Khan (Vancouver, Canada: University of British Columbia Press, 2007. 152 pages.) (American Journal of Islam and Society, 2008)
Using the role of an immigrant researcher in her country of origin, ShahnazKhan uses her feminist lens to explore dualities, decontextualization, andstereotypes of third-world women, more specifically Muslim women, whileexamining the contested issue of the ZinaOrdinance and itsmultifaceted consequencesfor women in Pakistan. Juxtaposing her feminist analysis withinthe context of transnational feminism, the author examines the tensions surroundingthis ordinance by questioning three intersecting contexts, namely, culture, politics, and religion. Pointing out such issues as corruption, maleviolence, poverty, and drug and alcohol abuse, Khan argues that the ordinanceallows families, in collaboration with the state, to regulate women’ssexuality. She reminds her readers that women charged with adultery and fornicationby the state are not victims, as they resist their incarceration in multipleways. Ironically, the prisons as well as the state-sponsored sheltersbecome safer spaces for women to flee the wrath of their families ...